Investigação da infecção por leishmania spp. Em felinos domésticos (felis catus) na cidade de Mossoró, Rio Grande do Norte - Bezerra, José Artur Brilhante (Universidade Federal Rural do Semi-Árido, 2019)
The aim of this study was to investigate the occurrence of Leishmania spp. infection and the coinfection by feline immunodeficiency virus (FIV) and feline leukemia virus (FeLV) in domestic cats from an area endemic for canine and human leishmaniosis in Rio Grande do Norte State, Brazil. Ninety-one cats were subjected to a complete clinical exam, and blood samples were collected. An epidemiological survey was used to investigate the risk factors. IgG anti-Leishmania spp. antibodies were detected by immunofluorescence antibody test (IFAT), with a cut-off value of 1:40. Polymerase chain reaction (PCR) was performed to detect genetic material of Leishmania spp. in the blood samples. The presence of antibodies against FIV and antigens of FeLV was evaluated using an immunochromatographic test. Seropositivity for Leishmania spp., FIV, and FeLV was observed in 14 (15.38%), 26 (28.57%), and 3 (3.29%) cats, respectively. All samples gave negative results on PCR analysis. No statistical association was observed between seropositivity for Leishmania spp., and sex, age, presence of clinical signs, and evaluated risk factors. Of the 14 animals seropositive for Leishmania spp., 5 presented antibodies against FIV; however, no association between Leishmania infection and FIV was observed (p = 0.052). None of the cats was co-infected by Leishmania spp. and FeLV. These findings demonstrated for the first time that cats from the studied region were being exposed to this zoonosis and might be part of the epidemiological chain of transmission of visceral leishmaniosis
Keywords: Leishmaniose; Retroviroses felinas; Zoonose; Epidemiologia; RIFI; Leishmaniosis; Feline retrovirusis; Zoonosis; Epidemiology; IFAT; CIENCIAS AGRARIAS::MEDICINA VETERINARIA